Pakistan: Strategy to promote climate smart agriculture practices - Rana, Abdul Wajid; Gill, Sitara (International Food Policy Research Institute, 2024)
Pakistan is a case of double injustice contributing a minuscule share of global greenhouse gases, yet it is bearing the brunt of global climate change impacts. It ranks among the top 10 countries vulnerable to climate change (Eckstein et al., 2021). The 2022 IPCC Report underlines the heightened vulnerabilities because of global warming and climate change leading to more floods. The Asia-Pacific Disaster Report 20221, Pakistan could lose more than 9 percent of its annual GDP due to climate change. The Notre Dame- Gain Matrix2 ranks Pakistan 5th most impacted country by climate change shocks and is positioned as the 36th least-prepared nation to cope with climate changes (The World Bank Group, 2021). Besides, Pakistan scores worst on the indicator of Agriculture Capacity3 at 0.939. Pakistan is highly vulnerable to climate changes because of its arid to semi-arid environmental conditions (Nasim et al., 2018; Ullah et al., 2019, Ghaffar et al., 2022). Over the last two decades, the country has been facing the challenges of rising temperature, extreme heatwaves, drought, intense and erratic precipitation, water stress, glacial melting, recurring flash floods and super floods in 2010 and 2022. The combination of reduced crop yields, water scarcity, and changing agricultural practices can lead to severe food insecurity and economic challenges for marginalized communities and more importantly, for farmers. In July-August 2022, Pakistan faced unprecedented rainfall and riverine floods damaging cultivated crops, livestock and the infrastructure. Approximately 4.4 million acres of crops were damaged, and nearly 1 million animals perished. The total cost of damages and losses was estimated at $30.13 billion, with agriculture accounting for $12.9 billion (43 percent of the total) (Economic Survey of Pakistan, 2021-22).